Impact of cover/bar diameter ratio to the structural performance of reinforced concrete member due to corrosion - Mohd Noh, Hamidun; Sonoda, Yoshimi (Penerbit Uthm, 2018)
Corrosion of steel in reinforced concrete is one of the main issues among construction stakeholders. The main consequences of steel corrosion include loss of cross section of steel area, generation of expansive pressure which caused cracking of concrete, spalling and delaminating of the concrete cover. Thus, it reduces the bond strength between the steel reinforcing bar and concrete, and deteriorating the strength of the structure. The objective of this study is to investigate the impact of c/d ratio to the structural performance of reinforced concrete member due to corrosion. A series of reinforced concrete cylinder of ϕ100mm x 200mm, ϕ150mm x 300mm and ϕ200mm x 400mm with c/d ratio of 2.13, 3.45 and 4.76 was modelled consisting of 19mm diameter of reinforcement bar at the center of the cylinder. Corrosion rate of 0%, 5% and 10% of rebar corrosion is used in parametric study to assess the influence of different level of corrosion rate to the structural performance. As a result, a positive linear relationship was sketched between the increase of expansive pressure and the corrosion rate for each c/d ratio. Meanwhile, the expansive pressure is inversely proportional to the c/d ratio due to the deflection effect in the larger concrete cover is smaller compared to the lower c/d ratio which is more severe. Furthermore, the analysis shows that there is a significant effect on the failure pressure for each c/d ratio as the failure pressure of lower c/d ratio increase proportionally with the increase of c/d ratio. This study could predict the structural deterioration by numerical analysis using the c/d ratio. Hence, the findings provide a good input in designing a structure which takes into account the c/d ratio and also the corrosion level of the structure.